1995
DOI: 10.1002/j.1552-4604.1995.tb04020.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Estimating Individualized Valproate Clearance Values in Children

Abstract: To evaluate the population pharmacokinetics of valproic acid in children, 97 steady-state serum valproate concentration measurements were gathered during normal, routine, outpatient care of 52 children with epilepsy (1.2-16 years of age). Levels were obtained from patients receiving valproate monotherapy (49%) or valproate with concomitant carbamazepine (32%), phenytoin (11%), or phenobarbitone (8%). A one-compartment model was used to fit the data with the Nonlinear Mixed Effects Model (NONMEM) computer progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
28
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 21 publications
7
28
0
6
Order By: Relevance
“…The linear relationship of TBW and age with CL of valproate was shown in the study. The facts that age and total body weight are the important factors that influence a change of VPA CL in children and also in heterogeneous patient populations were in accordance with reports of other authors [15][16][17].…”
Section: Valproatesupporting
confidence: 91%
See 4 more Smart Citations
“…The linear relationship of TBW and age with CL of valproate was shown in the study. The facts that age and total body weight are the important factors that influence a change of VPA CL in children and also in heterogeneous patient populations were in accordance with reports of other authors [15][16][17].…”
Section: Valproatesupporting
confidence: 91%
“…In agreement with our findings, results of numerous studies have shown that the relative clearance of valproate is increased in concomitant therapy with carbamazepine [15][16][17][18][19]. In children the increase in VPA clearance ranged from 35.9% to 61% [16,18].…”
Section: Valproatesupporting
confidence: 91%
See 3 more Smart Citations